The effect of rapid mixing on the break-up and re-formation of flocs - (:unkn) unknown (WILEY, 2004)
The effect of rapid mixing on floc formation, breakage and re-formation using aluminium sulfate ('alum'), polyaluminium chloride and a cationic polyelectrolyte were investigated using a continuous optical monitoring technique. For the aluminium-based coagulants it was found that, with shorter times of rapid mix, larger flocs were formed, but only limited re-growth occurred in all cases, indicating a significant irreversibility of the floc break-up process. For cationic polyelectrolytes, the re-growth of flocs occurred to a much greater extent and with longer rapid mix times floc breakage was almost fully reversible. Residual turbidity values before floc breakage and after re-formation were consistent with the dynamic monitoring results. (C) 2004 Society of Chemical Industry.
Keywords: floc breakage; floc strength; flocculation; hydrolysing coagulant; polyelectrolytes; rapid mix; COAGULATION; ALUM